Estudio de la concentración microbiana en el aire de depósitos del Archivo Nacional de Cuba - Borrego, Sofía (2009)
Nowadays, experts are interested in studying microbiota in indoor environments since microorganisms can produce human health disorders and biodeteriorate valuable collections. The aims of this paper were: to determine the microbial concentration of air in repositories of National Archive of Cuba, to carry out taxonomic identification of isolated fungi and to measure their potential risk for both the documentary heritage and staff's health. The microbiological sampling was conducted in summer and winter in 6 repositories by means of a sedimentation method. Petri dishes with adequate culture media placed in triplicate at a height of 3 m were used to isolate fungi and bacteria. Cellulolytic activity and production of pigments and acids by the isolated fungi were qualitatively determined. The total viable microbiota was greater in winter than in summer. Bacterial concentration was significantly higher in winter (dry season) whereas fungal concentration was greater in summer . Aspergillus , Cladosporium, Penicillium, Curvularia and Alternaria were the predominant fungal genera in winter while Cladosporium prevailed in summer together with genera such as Fusarium, Mucor and Chrysonilia, which in some repositories reached significant levels. On one hand, the isolated fungi degraded cellulose and produced pigments and acids. On the other hand, it was found that these fungi can provoke allergic states and respiratory diseases in humans. As to the bacteria present in the air, Gram positive ones prevailed: Enterobacter, Hafnia, Serratia, Streptomyces, Bacillus, Streptococcus and Staphylococcus. Moreover, we found that the identified bacteria can affect human health.